Exploration of laser-assisted chemical bath for enhancing synthesis of undoped and nickel-doped zinc oxide and its potential applications in water purification and mitigating antimicrobial resistance - Zyoud, Samer H.; Alalalmeh, Samer O.; Hegazi, Omar E.; Alami, Jamil H.; Che Abdullah, Che Azurahanim; Yahia, I.S.; Hassan, Nageeb; Ashames, Akram; Zahran, H. Y.; Bloukh, Samir Haj; Shahwan, Moyad; Zyoud, Ahed H.; et al. (Elsevier GmbH, 2024)
This study aims to explore the antimicrobial and photocatalytic efficiencies of pure and Ni-doped ZnO nanostructures produced via Laser-assisted Chemical Bath Synthesis (LACBS) to develop sustainable solutions for water treatment and pathogen control amid the global water crisis exacerbated by climate change and environmental pollution. Utilizing zinc acetate dihydrate and hexamethylenetetramine, the nanostructures were synthesized with Ni doping levels of 0.0 %, 1.5 %, 3.0 %, and 4.5 %, targeting their promising photocatalytic and antimicrobial properties to combat contaminants from pharmaceuticals, agriculture, and industries. Morphological analyses using Scanning Electron Microscopy showed a transition from hexagonal particles to nanoflowers, enhancing photocatalytic activity due to increased surface-to-volume ratio. X-ray Diffraction confirmed the hexagonal wurtzite structure, with variations in peak intensities indicating improved crystallinity with Ni doping. Energy Dispersive X-ray analysis verified the purity and successful incorporation of Ni. Photocatalytic assessments indicated up to 99.24 % degradation of Methylene Orange dye under blue laser irradiation within 60 minutes, correlating with Ni content. Antimicrobial tests demonstrated effective inhibition of pathogens such as Escherichia coli, Staphylococcus aureus, and additional strains like Candida albicans and Klebsiella pneumonia, with increasing zones of inhibition corresponding to higher Ni levels, extending up to 37 mm. The results underscore the dual functionality of ZnO nanostructures for applications in sustainable water treatment and antimicrobial controls, highlighting the need for future studies to examine the impacts of further increased doping concentrations on the material properties and efficacy.